Evaluation of Hematological Changes in The Pregnant Women in EL-Beyda City- Libya (Sirte Journal of Medical Sciences, 2024)
Background: Pregnant women normally undergo to several hematological changes perhaps anemia is considered the significant one. It is a major public health problem and commonly associated with many consequences as low birth weight, premature delivery and the increased risk of the maternal mortality and morbidity in the pregnant women, mainly in the developing countries.The aim of the study: The present study was designed to estimate the changes in hematological parameters in women during pregnancy at EL-Beyda City. Methods: Cross sectional study involved 350 randomly selected pregnant mothers who are attended several medical clinics in the period of February to July 2022,  of age group 17-48 years. A venous blood samples were collected in EDTA tubes and analyzed for complete blood counts (CBC) to evaluate hemoglobin levels (Hb), mean cell volume (MCV), mean cell hemoglobin (MCH), mean cell hemoglobin concentration (MCHC), white blood cells (WBCs) and platelets count. Other data were also reported including women age,  trimester of pregnancy, the number of the gravida and the parity. Results were obtained by analyzing collected data by SPSS version 26 and represented as mean ± SE and P value is considered significant when  it is less than 0.05. The Results: The mean age of the participants women was 29.5(±0.33), the overall prevalence of anemia was 57% and vast of them were in third trimester period. Out of 204 anemic women, 109 (53.4%) of them had normocytic normochromic anemia (mean of MCV 88fl).   while the rest 94 (46%) were suffered microcytic hypochromic anemia (mean of MCV 72fl). The present investigation was revealed that the mean of hemoglobin of anemic women was 9.84±0.06. which are significantly different in the mean of non-anemic women (p value =0.000) as well as majority of women 165 (81 %) had mild anemia (Hb= 9-10.9 g/dl). Conclusion: We can conclude that the prevalence of anemia in Libya in the studied population is considerably high in comparison to other countries, therefore the great awareness efforts are recommended to encourage a regular antenatal checkups